Influence of Auxins on Rooting Efficacy in Carnation (Dianthus caryophyllus L.) Cuttings - Ramesh Kumar (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2014)
Effect of various auxins (IBA, IAA and NAA) on different types of cuttings was investigated to determine efficacy of auxins in promoting rooting in carnation (Dianthus caryophyllus L.). Auxin and type of cutting significantly affected rooting traits. NAA was found to be more effective in promoting early rooting and inducing profuse rooting, root number, fresh and dry weight of roots and longer roots. Among the auxins used, earliest rooting (18.69 days), highest rooting percentage (58.70 %), number of roots (13.18), root length (12.26 cm), and, highest fresh and dry weight of roots (4.93g and 45.08 mg), respectively, were obtained with NAA @ 500 ppm. Tip cuttings responded better in rooting-characteristic of carnation - than basal cuttings, and recorded highest rooting percentage (73.02 %) and number of roots (12.25), longest roots (10.04cm) and maximum fresh and dry weight of roots (4.27 g and 43.19 mg), respectively. Interaction effect of auxin and cutting type was found to the significant, and highest rooting percentage, (85.26%), number of roots (18.36), longest roots (14.81cm), and highest fresh and dry weight of roots (6.85g and 68.02mg), respectively, observed with NAA @ 500 ppm in tip cuttings.